Contribuição ao estudo do sistema de pré-lajes tipo painel treliçado em pavimentos de edificações - Rocha, Filipe de Lima (2015)
The civil construction more than ever is challenged by the circumstances faced by the country, the economic crisis experienced in these last few years puts into perspective the necessity of more rational choices avoiding unnecessary dispenses and wastes. In face of this scenario the pre-cast elements became vital to guarantee the conclusion in less time and trying to reduce constructive bottlenecks. The latticed pre-cast concrete slabs are one of the many types of pre-cast parts which can be used at the construction sites, however the national standards are confuse and vague about some aspects contained especially in the European standards. Even the last review of the NBR 6118 of 2014 adds little about the issue and the more specific standard (NBR 14680) has few constructive details regarding the connection between elements and the calculus procedures, therefore this work tries to discuss the main questions related to this kind of pavement, introduces knowledge coming from other standards trying to answer some less usual doubts, but extremely pertinent ones such as, for example, the concept of self-portance, the use of this material in bridge floors and also the type connective reinforcement needed to attain the effective monolithism at the interface between beamstructure. This dissertation also presents some examples of pre- and post-constructive deflection limits, fissured deformation and a full example of calculation for a common pavement. Some data from the experiments realized at the NEPRE in the University of São Carlos and their practical application are shown as well.